Flying with the Mind: Mental Training to Support Ski Jumping and Nordic Combined. (Sport and Exercise Psychology, 2025)
Ski jumping and Nordic combined are among the most fascinating disciplines in Nordic Skiing: gliding down the jump ramp, athletes reach speeds of up to 90 km/h. Once they have reached this speed, they must perform a jump with their skis in a ‘V’ position during the flight phase and land using the Telemark technique. The cross-country skiing section of the Nordic combined transforms the gaps into a direct challenge in which the winner is the one who crosses the finish line first, adopting the best strategy: the audience is caught up in an adrenaline-filled atmosphere until the very last breath. The disciplines are carried out in highly challenging environments, in which the maximum expression of technical skill, motor control, emotional regulation and psychophysiological energies over several days are decisive. This chapter will present the fundamental technical aspects, combined with the mental aspects that have emerged from scientific research in the field of sports psychology, with the aim of highlighting how mental skills can support performance. Finally, there will be a focus on the impact that the use of technological doping and the need to maintain a low body weight can have on the development of sporting culture and the well-being of athletes. The aim is to provide an initial overview of the scientific research carried out to date, promoting the importance of psychologists trained in sports psychology in these disciplines, which are as fascinating as they are still little known.
Keywords: nordic skiing; sport psychology; mental skills; well-being; performance